(untitled) (Entrepreneurship Journal for Finance and Business, 2021)
The purpose of the current study is to determine the effect of marketing intelligence in promoting entrepreneurship in Jotun Modern Paints Company. The study was represented by two variables, including the independent variable, marketing intelligence in its dimensions (customer intelligence, market intelligence, product intelligence, competitor intelligence), while the dimensions of the dependent variable represented entrepreneurship with its three dimensions (proactive, innovation, risk bearing). The study population was represented in the Jotun Modern Paints Company and its branches located in the governorate of Baghdad. The intentional research sample, consisting of (65) individuals from the managers and workers of the above company, was also selected. The questionnaire was also used as a tool to obtain the necessary data that was prepared based on the ready-made measures after being subjected to it. In addition to the validity and reliability tests, the application (Microsoft Excel) and the statistical program (SPSS Ver.19) were used to enter and analyze the study data. The study presented a set of results, the most important of which was the existence of a positive relationship and a positive impact of marketing intelligence aimed at enhancing the entrepreneurship of the company throughout the study and research.